Human Resource Management (HR) to Customers in Bank Syariah Mandiri - Syafii, M.; Rahma, Aini (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2025)
Islamic banks in Indonesia have experienced good development in terms of assets, number of offices, number of customers, and the market share of Islamic banks has exceeded 5 percent. The development of Islamic banking is not accompanied by a sufficiently good human resource base in terms of quantity and quality. The source of human energy is still a difficult problem for Islamic banks. In the 2015-2019 Islamic banking roadmap issued as a financial service sovereign, the problem of people's resources becomes a matter that must be resolved. A pattern of human resources management is needed that can produce quality human resources for Islamic banks. This note is descriptive qualitative in nature which seeks to describe the development of quality human resources for Islamic banks. This note proves that there was a development of human resources in Islamic banks in the period 2015 September to September 2019 experiencing large and efficient developments, with the current overall HR of Islamic banks. The pattern of management of Islamic sources of energy is important for the availability of good quality Islamic banking human resources compatible with experts in the field of Islamic banking. Management of Islamic human resource base is able to fulfill human resources who understand economics and sharia economics. Islamic resource management that is relevant to the current situation of Islamic bank HR is Celestial Management. Which consists of ZIKR, PIKR, and MIKR.